On the History of the Kobzar-Lirnyk Tradition - Tovkailo, Mykola (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
This article presents a brief history of the development of the cultural phenomenon which is now called “kobzarstvo.” I analyze the Kobzar-Lirnyk singing tradition, musical instruments (kobza, bandura, wheel lyre), repertoire, forms of organization, modes of transmission, and other factors as they changed diachronically. I review sources to develop an understanding of their lifestyle and art. Over time, the mostly blind and itinerant kobzari developed their own world view and style of living. To organize and regulate their activities, to protect their rights, and for other advantages, they created self-governing territorial guilds, elected leaders, initiation rituals, and rules of conduct. Kobzarstvo was nearly eradicated in early Soviet times, but a few bearers of the tradition survived in the margins. The tradition has revived powerfully in the period of Ukrainian independence, with guilds, repertoire, initiation rituals and other elements re-established in the new cultural and technological context.